BOTHA, Anna Elizabeth Inventory of documents - BOTHA, Anna Elizabeth (ARCA, 2017)
Private papers of A.E. Botha, wife of State President P.W. Botha.
COVERAGE 1935-1976; 52 Files; 37,80 Metres.
Keywords: BOTHA, Anna Elizabeth; Inventories; Politicians; National Party